Implementing the Pacific Islands Regional Ocean Policy: How Difficult is it Going to Be? - Cordonnery, Laurence (Victoria University of Wellington Law Review, 2005)
This article discusses the challenges facing the Pacific region in implementing the Pacific Islands Regional Ocean Policy (PIROP), which aims to ensure sustainable use of the Pacific Ocean’s resources for the future. The author outlines some of the particular issues confronting Pacific Island countries, and the need for a more collaborative approach to ocean management. The five guiding principles of PIROP are then discussed in turn. These include: improving our understanding of the ocean; the sustainable development and management of the ocean’s resources; maintaining the health of the ocean; promoting the peaceful use of the ocean; and creating partnerships and promoting cooperation. Issues such as the protection of traditional knowledge in relation to the ocean, and the need to preserve the integrity of the Pacific’s ecosystems, are highlighted.